Pengaruh Inovasi Produk dan Harga terhadap Keputusan Pembelian Suzuki Karimun Wagon R AGS (Studi di Dealer United Motor Centre Jalan Ahmad Yani Surabaya) - TANJUNG TANDIA, ADITYA; SETYO IRIANI, SRI (Jurnal Ilmu Manajemen (JIM), 2018)
This study is based on the phenomenon of the gap, the gap when Suzuki issued Suzuki Karimun Wagon R AGS with various innovations invested and the lowest price but the lowest annual sales, even in every year sales decreased. The purpose of this study is to analyze and discuss the effect of product innovation and price on the purchase decision Suzuki Karimun Wagon R AGS. This study is a conclusive study. Using non probability sampling method The sampling method used is judgmental sampling with the number of 55 respondents. Technique of collecting data using questionnaire with closed statement and open question. This study uses the likert scale. The statistical analysis used is a multiple linear regression analysis with SPSS 23 for windows. The results showed that the variables of Product Innovation are significant effect on the purchases decision with significant value of 0,004. Price variables significantly influence the purchase decision with significant value of 0,009.